2019
DOI: 10.1332/239788219x15641291564296
|View full text |Cite
|
Sign up to set email alerts
|

Care poverty: unmet care needs in a Nordic welfare state

Abstract: This article introduces the concept of care poverty, defined as inadequate coverage of care needs resulting from an interplay between individual and societal factors, and examines its level and predictors among the 75+ population in Finland. The data come from a survey conducted in 2010 and 2015. Despite the universalistic goals of the Finnish care system, 26 percent of respondents with limitations in daily activities faced care poverty with regard to instrumental activities of daily living; the activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 24 publications
1
70
0
Order By: Relevance
“…More in-depth research is needed to assess the ability of home care and other support services to provide adequate care for home-dwelling older people at the end of life. A recent study of home care workers’ reflections on their work (Kröger, Van, Aerschot, & Puthenparambil, 2018) suggest that their increasingly demanding work with clients with multiple care needs has not been taken thoroughly into account in home care planning. It might also be necessary to add to the resources available for round-the-clock LTC to guarantee good-quality end-of-life care for the older population, given that formal home care topped up with informal care is not available to everyone.…”
Section: Discussionmentioning
confidence: 99%
“…More in-depth research is needed to assess the ability of home care and other support services to provide adequate care for home-dwelling older people at the end of life. A recent study of home care workers’ reflections on their work (Kröger, Van, Aerschot, & Puthenparambil, 2018) suggest that their increasingly demanding work with clients with multiple care needs has not been taken thoroughly into account in home care planning. It might also be necessary to add to the resources available for round-the-clock LTC to guarantee good-quality end-of-life care for the older population, given that formal home care topped up with informal care is not available to everyone.…”
Section: Discussionmentioning
confidence: 99%
“…Policy goals should therefore include recognising coping strategies and strengthening positive coping strategies. Policies must be assessed not only by the resources they use or how many services they provide, but also by whether they achieve their objectives (see [42]). Research on family relations and well-being in the caregiving context within multigenerational households showed that care issues are an important issue in family conflicts [43] and that this is insufficiently addressed by public policies.…”
Section: Coping Strategies: Related Literaturementioning
confidence: 99%
“…Similar policies are favoured in many countries (Iecovich, 2014). As the number of people staying at home with less-formal care is increasing rapidly (Alastalo et al, 2017;Kröger et al, 2019), it is vital to discover new means of meeting the holistic needs of the ageing population.…”
Section: Introductionmentioning
confidence: 99%